Development Strategy of Creative Economy-Based Village: A Case Study of Kandri Tourism Village in Semarang Regency - Adhi Susano; Sutrisno Sutrisno; Pudji Astuty (CV. Publikasi Indonesia, 2022)
The Implementation of e-government in Village Governments can be the main intervention in driving villages towards progress. This type of research is Descriptive Research. The approaches used are qualitative and conceptual approaches. The data source used is secondary data. Data analysis is carried out descriptively and qualitatively. Conclusions are drawn using deductive methods, which means drawing conclusions from general to specific, especially related to the research topic, namely the Development Strategy of Creative Economy-Based Tourism Villages. This research yields findings that the implementation of social media and digitalization in Kandri tourism village has been very effective. Visitors can easily obtain information about the tourism village and directly fill out online reservation forms, complete with available tour packages. Emphasizing the concept of